FMX – the Frontier Microfocusing Macromolecular Crystallography Beamline at the National Synchrotron Light Source II - Schneider, Dieter K. (J Synchrotron Radiat, 2021)
Two new macromolecular crystallography (MX) beamlines at the National Synchrotron Light Source II, FMX and AMX, opened for general user operation in February 2017 [Schneider et al. (2013 ▸). J. Phys. Conf. Ser. 425, 012003; Fuchs et al. (2014 ▸). J. Phys. Conf. Ser. 493, 012021; Fuchs et al. (2016 ▸). AIP Conf. Proc. SRI2015, 1741, 030006]. FMX, the micro-focusing Frontier MX beamline in sector 17-ID-2 at NSLS-II, covers a 5–30 keV photon energy range and delivers a flux of 4.0 × 10(12) photons s(−1) at 1 Å into a 1 µm × 1.5 µm to 10 µm × 10 µm (V × H) variable focus, expected to reach 5 × 10(12) photons s(−1) at final storage-ring current. This flux density surpasses most MX beamlines by nearly two orders of magnitude. The high brightness and microbeam capability of FMX are focused on solving difficult crystallographic challenges. The beamline’s flexible design supports a wide range of structure determination methods – serial crystallography on micrometre-sized crystals, raster optimization of diffraction from inhomogeneous crystals, high-resolution data collection from large-unit-cell crystals, room-temperature data collection for crystals that are difficult to freeze and for studying conformational dynamics, and fully automated data collection for sample-screening and ligand-binding studies. FMX’s high dose rate reduces data collection times for applications like serial crystallography to minutes rather than hours. With associated sample lifetimes as short as a few milliseconds, new rapid sample-delivery methods have been implemented, such as an ultra-high-speed high-precision piezo scanner goniometer [Gao et al. (2018 ▸). J. Synchrotron Rad. 25, 1362–1370], new microcrystal-optimized micromesh well sample holders [Guo et al. (2018 ▸). IUCrJ, 5, 238–246] and highly viscous media injectors [Weierstall et al. (2014 ▸). Nat. Commun. 5, 3309]. The new beamline pushes the frontier of synchrotron crystallography and enables users to determine structures from difficult-to-crystallize targets like membrane proteins, using previously intractable crystals of a few micrometres in size, and to obtain quality structures from irregular larger crystals.